Numerical and experimental investigation of scaling laws in PLA octet-truss lattice structures under compression load - Muhammad Yusri Dzal Yahya; Agus Sigit Pramono (Politeknik Negeri Lhokseumawe, 2025)
The demand for lightweight materials with superior strength-to-weight ratios in modern industry has driven innovation in architectural materials. Lattice structures, enabled by advances in Additive Manufacturing (AM), present a promising solution. However, their mechanical performance often deviates from theoretical predictions due to the complexity of the fabrication process, particularly in Fused Deposition Modeling (FDM) technology, which is prone to process defects and size effects. This study aims to address the discrepancy between scaling-law predictions and the actual mechanical response of an Octet-Truss lattice structure fabricated from Polylactic Acid (PLA) using FDM. This study specifically investigates the effects of geometric scaling up/down (0.75x, 1x, and, 1.25x) and the number of periodic unit cells (1 - 8) on compressive response up to the yield limit. To validate the compression behavior, this study combined Finite Element Analysis (FEA) with experimental compression testing of FDM-fabricated PLA specimens. A highly accurate linear regression model (RÂ² 99.7%) was formulated, relating maximum compression force (Fmax) to the number of unitcells (ncell), with FEA predictions aligning with experimental results within a 1.70% error margin. This empirical scaling law facilitates accurate predictions of load-bearing capacity across a range of lattice configurations (with cell sizes ranging from 15 to 25 mm cell sizes ) and load predictions ranging from 312 to 2,847 N for all tested configurations. This contributes to the development of a practical and reliable predictive design tool for lightweight structural engineering applications.